Social policy responses to COVID‐19 in Canada and the United States: Explaining policy variations between two liberal welfare state regimes. (1st November 2020) - Béland, Daniel; Dinan, Shannon; Rocco, Philip; Waddan, Alex
Abstract: Canada and the United States are often grouped together as liberal welfare‐state regimes, with broadly similar levels of social spending. Yet, as the COVID‐19 pandemic reveals, the two countries engage in highly divergent approaches to social policymaking during a massive public health emergency. Drawing on evidence from the first 5 months of the pandemic, this article compares social policy measures taken by the United States and Canadian governments in response to COVID‐19. In general, we show that Canadian responses were both more rapid and comprehensive than those of the United States. This variation, we argue, can be explained by analysing the divergent political institutions, pre‐existing policy legacies, and variations in cross‐partisan consensus, which have all shaped national decision‐making in the middle of the crisis.